Experiences With Help Seeking Among Non–Service-Engaged Survivors of IPV: Survivors’ Recommendations for Service Providers - Voth Schrag, Rachel J. (Violence against women, 2021)
Engaging with formal intimate partner violence (IPV) services can buffer the impacts of violence and reduce future risk. Many survivors do not access or engage with such services. However, much of our knowledge related to the experiences and perspectives of IPV survivors comes from samples drawn from those seeking formal services. Qualitative interviews with 23 survivors of violence who are not currently engaged with formal IPV services were conducted, focused on the process and outcomes of choosing to seek help. Themes emerged within the categories of formal help-seeking experiences, informal help seeking, and recommendations for providers.